2017
DOI: 10.21037/jtd.2017.02.64
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response in a critical lung adenocarcinoma presenting as large airway stenoses after receiving stent implantation and sequential rebiopsy guided ALK inhibitor therapy: a case report

Abstract: Airway stent implantation can improve the symptoms of airway stenosis caused by a malignant tumor immediately. However, stent implantation is only a palliative therapy and disease will quickly progress without subsequent treatment. Targeted therapy can provide accurate etiological treatment for patients with critical lung cancer who cannot receive chemotherapies. In our clinic, we encountered a 50-year-old male presenting with stage IV lung adenocarcinoma. He failed both the first-line and second-line chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…These stents can also be safely removed from patients who require stent removal, similar to silicone stents 1,2 . Few similar reports exist on combination therapy with molecular‐targeted agents and an airway stents 4–7 . It has been reported that airway stenosis in an ALK‐positive lung cancer case with severe airway stenosis improved after ALK‐TKI treatment and temporary placement of a silicone Y‐stent, which was removed 5–6 months later 5,6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These stents can also be safely removed from patients who require stent removal, similar to silicone stents 1,2 . Few similar reports exist on combination therapy with molecular‐targeted agents and an airway stents 4–7 . It has been reported that airway stenosis in an ALK‐positive lung cancer case with severe airway stenosis improved after ALK‐TKI treatment and temporary placement of a silicone Y‐stent, which was removed 5–6 months later 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Few similar reports exist on combination therapy with molecular‐targeted agents and an airway stents. 4 , 5 , 6 , 7 It has been reported that airway stenosis in an ALK‐positive lung cancer case with severe airway stenosis improved after ALK‐TKI treatment and temporary placement of a silicone Y‐stent, which was removed 5–6 months later. 5 , 6 Furthermore, there have been reports on AERO stent removal due to the effects of immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting oncogenic drivers of disease may possibly result in rapid and profound treatment responses that can potentially reverse oncologic burden and improve patient outcomes. For example, the literature demonstrates that targeting ALK , EGFR , and BRAF gene mutations have resulted in remarkable responses in critical patients [ 11 14 ].…”
Section: Discussionmentioning
confidence: 99%